Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

16.(2-3x)+x^2.(3x-2)=0

Sagot :

Tasyha

Answer:

[tex] x_{1} = - 1 \: . \: \: x_{2} = \frac{2}{3} . \: \: x_{3} = 1 [/tex]

Step-by-step explanation:

[tex](2 - 3x) + {x}^{2} (3x - 2) = 0 \\ 2 - 3x + {x}^{3} - 2 {x}^{2} = 0 \\ - (3x - 2) + {x}^{2} (3x - 2) = 0 \\ - (3x - 2)(1 - {x}^{2} ) = 0 \\ (3x - 2)(1 - {x}^{2} ) = 0 \\ 3x - 2 = 0 \\ 1 - {x}^{2} = 0 \\ x = \frac{3}{2} \\ x = - 1 \\ x = 1 \\ [/tex]

[tex]\boxed{\green{ x_{1} = - 1 \: . \: \: x_{2} = \frac{2}{3} . \: \: x_{3} = 1}}[/tex]

We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.